2020
DOI: 10.1111/ijcs.12568
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of consumer empowerment on the relationship between involvement in eco‐friendly food and eco‐friendly food behaviour

Abstract: This study investigates the moderating effect of consumer empowerment on the relationship between involvement in and purchase behaviour towards eco‐friendly food. It uses the generalized linear model, with data from the 2017 Research on Food Consumption. The results showed that gender is related only to involvement in eco‐friendly food and this involvement is higher for women than for men. Moreover, involvement in eco‐friendly food, purchase empowerment, engagement empowerment and frequency of buying eco‐frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
(54 reference statements)
3
27
0
Order By: Relevance
“…Product retention is often considered and encouraged in public policy endeavours undertaken for the purpose of encouraging environmentally friendly (green) consumption and reducing waste/increasing recycling (Fuentes, 2014; Nam, 2020). However, while green consumer values are related to self‐control in spending and frugality (Haws et al., 2014), they are also negatively related to materialism (Banerjee & McKeage, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Product retention is often considered and encouraged in public policy endeavours undertaken for the purpose of encouraging environmentally friendly (green) consumption and reducing waste/increasing recycling (Fuentes, 2014; Nam, 2020). However, while green consumer values are related to self‐control in spending and frugality (Haws et al., 2014), they are also negatively related to materialism (Banerjee & McKeage, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of SRT, consumers who believe they are able to contribute effectively towards saving the environment update their attitude in line with this belief in order to pursue their goals. This self‐regulatory process is considered strong enough, as the consumers and the environment are interdependent (Burhanudin & Ferguson, 2018; Nam, 2020). Furthermore, the standard of greenness is clear amongst consumers (Bryson et al., 2016; Ellen et al., 1991; Kang et al., 2013; Kautish et al., 2019), which helps to motivate them to update their attitude towards green banking (Bryson et al., 2016).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Although companies using both part of food label simultaneously nevertheless the results regarding efficacy of both labels are inconsistence. The food processing companies following their concern GOVT policies for describing the nutritional information at both food label formats but the policy can only effective when consumer consult food label at point of purchase (Nam, 2020). In addition to the aforementioned studies reported that consumer's opinions about food label efficacy differ from country to country as well as product to product.…”
Section: Food Label Reading Efficacy and Healthy Packaged Food Intentionmentioning
confidence: 99%